Hepatoprotective activity of polyhydroxylated 2-styrylchromones against tert-butylhydroperoxide induced toxicity in freshly isolated rat hepatocytes - Fernandes, Eduarda (2011)
2-Styrylchromones are a novel class of chromones, vinylogues of flavones (2-phenylchromones), which have recently been found in nature. The best described property of almost every group of flavones and other flavonoids, especially the hydroxylated derivatives, is their capacity to act as antioxidants. Indeed there is a widely accepted view that the positive health effects of flavones are due to their antioxidant activity. As oxidative stress is a main cause of liver toxicity induced by several hepatotoxicants, agents with the ability to protect the liver against reactive pro-oxidant species may be therapeutically useful. The present study evaluated the possible protective activity of six new synthetic polyhydroxylated 2-styrylchromone derivatives against the pro-oxidant hepatotoxicity exerted by tert-butylhydroperoxide (t-BHP) in freshly isolated rat hepatocytes. The cells were preincubated with the 2-styrylchromones in the final concentrations of 3.125, 12.5, 25, 50, 100, and 200 lM for 5 min before treatment with 1.0 mM t-BHP for 30 min (throughout this incubation period the cells were exposed to both compounds). The well-known antioxidant 3-hydroxyflavone (quercetin) was used as positive control. At the end of the 30-min incubation period, aliquots of cells suspensions were taken for measurement of lactate dehydrogenase leakage, thiobarbituric acid reactive substances, reduced glutathione, and oxidized glutathione contents. The tested compounds exhibited in vitro protective activity against t-BHP induced hepatotoxicity (1.0 mM, 30 min). Three of the tested compounds, at the concentrations of 3.125, 12.5, 25, and 50 lM, prevented the t-BHP induced glutathione depletion, lipid peroxidation, and cell death in freshly isolated rat hepatocytes to a comparable potency with that of quercetin.